NGOs and Social Media: A Study of Content for Social Change in Spain and Chile - Ferruz González, Sonia Aránzazu; Claro Montes, María Cecilia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Comparative study of the publications on Facebook, Instagram, Youtube, X and Tiktok of NGOs in Chile and Spain to find out whether their profiles help to promote activism in social issues and what type of visual content they use. The methodology was mixed with a quantitative-qualitative approach: analysis of 3,611 publications from 20 organisations complemented by 12 in-depth interviews with the organisations' communication managers. The results show that photos are the most used content in all the networks, but only two Spanish NGOs use the networks with an activist objective.